Some effects of institutional reform on mechanisms of land, labor and animal traction use in the Ethiopian highlands - Omiti, J.; Ehui, Simeon K.; Parton, K.; Nokoe, S. (Lit Verlag Munster-Hamburg, 1996)
Some evidence of encouraging changes in rural land and labour use systems that are indicative of evolving and perhaps sustainable agricultural production in Ethiopia is provided from a 1993 survey of 228 households in seven villages in the central Ethiopian highlands. Information is discussed that serves to support the need to adjust policy reforms to consider the socioeconomic and cultural realities or rural peasant life if any changes are to remain compatible with public agricultural policy goals. Within household factor endowments and farming practices, the paper discusses: land use; agricultural labour and animal traction; land productivity and farming practices; and a policy towards integrated agricultural improvement.